ФРАНЦУЗСКИЙ ЯЗЫК КАК СРЕДСТВО ПРОФЕССИОНАЛЬНО- ОРИЕНТИРОВАННОГО МЕЖКУЛЬТУРНОГО ОБЩЕНИЯ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The problem of professionally oriented teaching of foreign languages is in the center of attention of modern scientists and is becoming increasingly important. The goal of professionally oriented French language training for bachelors in the field of “Tourism” is the formation of professional foreign language competencies in intercultural communication, the ability to interpret information in French and communicate with representatives of French- speaking countries.
Keywords: French; bachelor's degree; tourism; intercultural communication; interdisciplinary connections; linguistic and regional studies; interactive training.